Investigating Emotion Perception via the Two-Dimensional Affect and Feeling Space: An Example of a Cross-Cultural Study Among Chinese and Non-Chinese Participants - Lorette, Pernelle (Frontiers in Psychology, 2021)
The categorical approach to cross-cultural emotion perception research has mainly relied on constrained experimental tasks, which have arguably biased previous findings and attenuated cross-cultural differences. On the other hand, in the constructionist approach, conclusions on the universal nature of valence and arousal have mainly been indirectly drawn based on participants' word-matching or free-sorting behaviors, but studies based on participants' continuous valence and arousal ratings are very scarce. When it comes to self-reports of specific emotion perception, constructionists tend to rely on free labeling, which has its own limitations. In an attempt to move beyond the limitations of previous methods, a new instrument called the Two-Dimensional Affect and Feeling Space (2DAFS) has been developed. The 2DAFS is a useful, innovative, and user-friendly instrument that can easily be integrated in online surveys and allows for the collection of both continuous valence and arousal ratings and categorical emotion perception data in a quick and flexible way. In order to illustrate the usefulness of this tool, a cross-cultural emotion perception study based on the 2DAFS is reported. The results indicate the cross-cultural variation in valence and arousal perception, suggesting that the minimal universality hypothesis might need to be more nuanced.